Euro Brand Trust Factors in Building Consumer Loyalty of Household Goods Consumers - Hidayat, Z.; Teguh, Monika; Herdono, Ignatius Ismojo (International Review of Management and Marketing, 2025)
The context of global marketing communication of the Euro household brands is the focus of this research article. This study examines the effect of customer experience, perceived quality, brand associations, and European brand trust on customer satisfaction and loyalty. The survey was conducted in Greater Jakarta, Indonesia. This study took 452 samples in clusters to the profiles of married women and men who consumed Europe branded household products. The data were processed using the Amos structural equation model (SEM) version 26.0 to test several hypotheses. The study found that customer experience significantly influences perceived quality, brand association, European brand trust, customer satisfaction, and brand loyalty. Likewise, other variables, such as perceived quality, brand association, and European brand trust, significantly affect customer satisfaction and brand loyalty indirectly and directly. Trust in European brands shows a high-quality perception of European home appliances products. This psychological aspect may grow from the sociological experience that the Southeast Asian population and cultural heritage place quality European products in this region. The implications of the results of this study indicate that customer experience is networked as a basis in marketing communications for European brands in areas with a target market that has a history with Europe.